Spurious T3 Toxicosis in Multiple Myeloma: A Case Report: Spurious T3 Toxicosis in Multiple Myeloma - Hasan, Md Rakibul (Journal of the Medical College for Women & Hospital, 2025)
Alteration of thyroid function tests (TFT) may be seen in apparently healthy individuals in the presence of many drugs, chemicals, and vitamins in abnormal concentration in blood. Presence of plasma protein in high concentration (e.g., paraprotein) may affect the TFT by altering the binding capacity, giving rise to high concentration of total triiodothyronine (TT3) and total thyroxine (TT4) with normal concentration of free hormones (FT3, FT4). Here is a case report of a 25-year-old clinically euthyroid man without previous personal or family history of thyroid disease.He was referred to the endocrinologist for evaluation of inappropriately high TT3 >8.0 ng/ml (Reference range: 0.6-1.81) in the presence of normal TSH, TT4 concentration. He was diagnosed as a case of multiple myeloma (MM) five months back, receiving chemotherapy (Bortezomib and cyclophosphamide). The patient was clinically euthyroid, and his free T3 (FT3) was checked and was found to be within the normal reference range (FT3=3.03pg/ml; reference range 2.3-4.2). He was not taking any drugs (e.g., Tamoxifen, Biotin, Estrogen, Clofibrate, 5-Fluorouracil, Methadone) concomitantly that may interfere with the thyroid function test reports. He had normal liver function test reports with mild impairment of renal function (Serum Creatinine level: 1.48mg/dl, eGFR:58 ml/min/1.73m2). The patient was on follow-up without specific treatment for abnormal TFT, ensuring that the abnormal TFT report was due to paraproteinemia, which must be interpreted cautiously in such a situation. J Med Coll Women Hosp.2025; 21 (2):163-165